Area-Based Beef Cattle Farming Spatial Planning in Lampung Province - Putra, Boby Arya; Yulia, Yulia; Santi, Melia Afnida; Arfa'i, Arfa'i (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2024)
Livestock areas are areas specifically designated for livestock activities or integrated as a component of farming. The Beef Cattle Livestock development program is faced with the problem of increasingly narrow business land due to increasing competition in land use which results in the land available for green animal feed becoming increasingly narrow. Lampung Province has an area of 33,575.41 Ha with hilly and mountainous topography making it suitable for livestock development, beef production of 21.18 million kg/year, and has large land potential for development. while the beef cattle population is 906,568 heads. With this potential, it is very possible for Lampung Province to become a region for developing beef cattle farming. However, the problem is that Lampung Province does not yet have mapping and standards for spatial planning or beef cattle farming areas. This research was carried out by identifying and analyzing the potential for beef cattle development in Lampung Province using 2 analyzes namely; Descriptive Analysis, and Location Quation (LQ) Analysis. LQ analysis is used to determine the areas of beef cattle livestock centers in districts/cities in Lampung Province. The results of the research show that there are 14 regencies/cities that can be used as business centers for the maintenance and development of beef cattle in Lampung Province. Of the 15 regencies/cities in Lampung Province, only Bandar Lampung City has an LQ value of less than 1. The results of this research can become a reference for the Lampung Provincial government, related agencies and other stakeholders in making policy decisions for developing beef cattle businesses in Lampung Province in the future.